At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Certainly! We can solve these quadratic equations using the quadratic formula, which is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] are the coefficients from the general form of the quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex].
Let's go through each of the equations step-by-step.
### 1. Solve [tex]\(5h^2 - 2h - 7 = 0\)[/tex]
The equation is already in the standard form [tex]\(ah^2 + bh + c = 0\)[/tex] with:
- [tex]\(a = 5\)[/tex]
- [tex]\(b = -2\)[/tex]
- [tex]\(c = -7\)[/tex]
Using the quadratic formula:
[tex]\[ h = \frac{-(-2) \pm \sqrt{(-2)^2 - 4 \cdot 5 \cdot (-7)}}{2 \cdot 5} \][/tex]
[tex]\[ h = \frac{2 \pm \sqrt{4 + 140}}{10} \][/tex]
[tex]\[ h = \frac{2 \pm \sqrt{144}}{10} \][/tex]
[tex]\[ h = \frac{2 \pm 12}{10} \][/tex]
Finding the two solutions:
[tex]\[ h_1 = \frac{2 + 12}{10} = \frac{14}{10} = 1.4 \][/tex]
[tex]\[ h_2 = \frac{2 - 12}{10} = \frac{-10}{10} = -1 \][/tex]
So, the solutions are [tex]\(h = 1.4\)[/tex] and [tex]\(h = -1\)[/tex].
### 2. Solve [tex]\(6x^2 + x - 15 = 0\)[/tex]
The equation is already in the standard form [tex]\(ax^2 + bx + c = 0\)[/tex] with:
- [tex]\(a = 6\)[/tex]
- [tex]\(b = 1\)[/tex]
- [tex]\(c = -15\)[/tex]
Using the quadratic formula:
[tex]\[ x = \frac{-1 \pm \sqrt{1^2 - 4 \cdot 6 \cdot (-15)}}{2 \cdot 6} \][/tex]
[tex]\[ x = \frac{-1 \pm \sqrt{1 + 360}}{12} \][/tex]
[tex]\[ x = \frac{-1 \pm \sqrt{361}}{12} \][/tex]
[tex]\[ x = \frac{-1 \pm 19}{12} \][/tex]
Finding the two solutions:
[tex]\[ x_1 = \frac{-1 + 19}{12} = \frac{18}{12} = 1.5 \][/tex]
[tex]\[ x_2 = \frac{-1 - 19}{12} = \frac{-20}{12} = -\frac{5}{3} \][/tex]
So, the solutions are [tex]\(x = 1.5\)[/tex] and [tex]\(x = -\frac{5}{3}\)[/tex].
### 3. Solve [tex]\(3x^2 + 25x - 18 = 0\)[/tex]
The equation is already in the standard form [tex]\(ax^2 + bx + c = 0\)[/tex] with:
- [tex]\(a = 3\)[/tex]
- [tex]\(b = 25\)[/tex]
- [tex]\(c = -18\)[/tex]
Using the quadratic formula:
[tex]\[ x = \frac{-25 \pm \sqrt{25^2 - 4 \cdot 3 \cdot (-18)}}{2 \cdot 3} \][/tex]
[tex]\[ x = \frac{-25 \pm \sqrt{625 + 216}}{6} \][/tex]
[tex]\[ x = \frac{-25 \pm \sqrt{841}}{6} \][/tex]
[tex]\[ x = \frac{-25 \pm 29}{6} \][/tex]
Finding the two solutions:
[tex]\[ x_1 = \frac{-25 + 29}{6} = \frac{4}{6} = \frac{2}{3} \][/tex]
[tex]\[ x_2 = \frac{-25 - 29}{6} = \frac{-54}{6} = -9 \][/tex]
So, the solutions are [tex]\(x = \frac{2}{3}\)[/tex] and [tex]\(x = -9\)[/tex].
### 4. Solve [tex]\(2x^2 - 7x + 6 = 0\)[/tex]
The equation is already in the standard form [tex]\(ax^2 + bx + c = 0\)[/tex] with:
- [tex]\(a = 2\)[/tex]
- [tex]\(b = -7\)[/tex]
- [tex]\(c = 6\)[/tex]
Using the quadratic formula:
[tex]\[ x = \frac{7 \pm \sqrt{(-7)^2 - 4 \cdot 2 \cdot 6}}{2 \cdot 2} \][/tex]
[tex]\[ x = \frac{7 \pm \sqrt{49 - 48}}{4} \][/tex]
[tex]\[ x = \frac{7 \pm \sqrt{1}}{4} \][/tex]
[tex]\[ x = \frac{7 \pm 1}{4} \][/tex]
Finding the two solutions:
[tex]\[ x_1 = \frac{7 + 1}{4} = \frac{8}{4} = 2 \][/tex]
[tex]\[ x_2 = \frac{7 - 1}{4} = \frac{6}{4} = \frac{3}{2} \][/tex]
So, the solutions are [tex]\(x = 2\)[/tex] and [tex]\(x = \frac{3}{2}\)[/tex].
In summary, the truth sets for the given equations are:
1. [tex]\(5h^2 - 2h - 7 = 0\)[/tex] yields [tex]\(h = -1, 1.4\)[/tex]
2. [tex]\(6x^2 + x - 15 = 0\)[/tex] yields [tex]\(x = -\frac{5}{3}, 1.5\)[/tex]
3. [tex]\(3x^2 + 25x - 18 = 0\)[/tex] yields [tex]\(x = -9, \frac{2}{3}\)[/tex]
4. [tex]\(2x^2 - 7x + 6 = 0\)[/tex] yields [tex]\(x = 2, \frac{3}{2}\)[/tex]
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] are the coefficients from the general form of the quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex].
Let's go through each of the equations step-by-step.
### 1. Solve [tex]\(5h^2 - 2h - 7 = 0\)[/tex]
The equation is already in the standard form [tex]\(ah^2 + bh + c = 0\)[/tex] with:
- [tex]\(a = 5\)[/tex]
- [tex]\(b = -2\)[/tex]
- [tex]\(c = -7\)[/tex]
Using the quadratic formula:
[tex]\[ h = \frac{-(-2) \pm \sqrt{(-2)^2 - 4 \cdot 5 \cdot (-7)}}{2 \cdot 5} \][/tex]
[tex]\[ h = \frac{2 \pm \sqrt{4 + 140}}{10} \][/tex]
[tex]\[ h = \frac{2 \pm \sqrt{144}}{10} \][/tex]
[tex]\[ h = \frac{2 \pm 12}{10} \][/tex]
Finding the two solutions:
[tex]\[ h_1 = \frac{2 + 12}{10} = \frac{14}{10} = 1.4 \][/tex]
[tex]\[ h_2 = \frac{2 - 12}{10} = \frac{-10}{10} = -1 \][/tex]
So, the solutions are [tex]\(h = 1.4\)[/tex] and [tex]\(h = -1\)[/tex].
### 2. Solve [tex]\(6x^2 + x - 15 = 0\)[/tex]
The equation is already in the standard form [tex]\(ax^2 + bx + c = 0\)[/tex] with:
- [tex]\(a = 6\)[/tex]
- [tex]\(b = 1\)[/tex]
- [tex]\(c = -15\)[/tex]
Using the quadratic formula:
[tex]\[ x = \frac{-1 \pm \sqrt{1^2 - 4 \cdot 6 \cdot (-15)}}{2 \cdot 6} \][/tex]
[tex]\[ x = \frac{-1 \pm \sqrt{1 + 360}}{12} \][/tex]
[tex]\[ x = \frac{-1 \pm \sqrt{361}}{12} \][/tex]
[tex]\[ x = \frac{-1 \pm 19}{12} \][/tex]
Finding the two solutions:
[tex]\[ x_1 = \frac{-1 + 19}{12} = \frac{18}{12} = 1.5 \][/tex]
[tex]\[ x_2 = \frac{-1 - 19}{12} = \frac{-20}{12} = -\frac{5}{3} \][/tex]
So, the solutions are [tex]\(x = 1.5\)[/tex] and [tex]\(x = -\frac{5}{3}\)[/tex].
### 3. Solve [tex]\(3x^2 + 25x - 18 = 0\)[/tex]
The equation is already in the standard form [tex]\(ax^2 + bx + c = 0\)[/tex] with:
- [tex]\(a = 3\)[/tex]
- [tex]\(b = 25\)[/tex]
- [tex]\(c = -18\)[/tex]
Using the quadratic formula:
[tex]\[ x = \frac{-25 \pm \sqrt{25^2 - 4 \cdot 3 \cdot (-18)}}{2 \cdot 3} \][/tex]
[tex]\[ x = \frac{-25 \pm \sqrt{625 + 216}}{6} \][/tex]
[tex]\[ x = \frac{-25 \pm \sqrt{841}}{6} \][/tex]
[tex]\[ x = \frac{-25 \pm 29}{6} \][/tex]
Finding the two solutions:
[tex]\[ x_1 = \frac{-25 + 29}{6} = \frac{4}{6} = \frac{2}{3} \][/tex]
[tex]\[ x_2 = \frac{-25 - 29}{6} = \frac{-54}{6} = -9 \][/tex]
So, the solutions are [tex]\(x = \frac{2}{3}\)[/tex] and [tex]\(x = -9\)[/tex].
### 4. Solve [tex]\(2x^2 - 7x + 6 = 0\)[/tex]
The equation is already in the standard form [tex]\(ax^2 + bx + c = 0\)[/tex] with:
- [tex]\(a = 2\)[/tex]
- [tex]\(b = -7\)[/tex]
- [tex]\(c = 6\)[/tex]
Using the quadratic formula:
[tex]\[ x = \frac{7 \pm \sqrt{(-7)^2 - 4 \cdot 2 \cdot 6}}{2 \cdot 2} \][/tex]
[tex]\[ x = \frac{7 \pm \sqrt{49 - 48}}{4} \][/tex]
[tex]\[ x = \frac{7 \pm \sqrt{1}}{4} \][/tex]
[tex]\[ x = \frac{7 \pm 1}{4} \][/tex]
Finding the two solutions:
[tex]\[ x_1 = \frac{7 + 1}{4} = \frac{8}{4} = 2 \][/tex]
[tex]\[ x_2 = \frac{7 - 1}{4} = \frac{6}{4} = \frac{3}{2} \][/tex]
So, the solutions are [tex]\(x = 2\)[/tex] and [tex]\(x = \frac{3}{2}\)[/tex].
In summary, the truth sets for the given equations are:
1. [tex]\(5h^2 - 2h - 7 = 0\)[/tex] yields [tex]\(h = -1, 1.4\)[/tex]
2. [tex]\(6x^2 + x - 15 = 0\)[/tex] yields [tex]\(x = -\frac{5}{3}, 1.5\)[/tex]
3. [tex]\(3x^2 + 25x - 18 = 0\)[/tex] yields [tex]\(x = -9, \frac{2}{3}\)[/tex]
4. [tex]\(2x^2 - 7x + 6 = 0\)[/tex] yields [tex]\(x = 2, \frac{3}{2}\)[/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.